Nutrient composition, in vitro true digestibility (IVTD) and methane production potential of fodder tree leaves - RAMACHANDRAN, M; BHARATHIDHASAN, A; BALAKRISHNAN, V (The Indian Journal of Animal Sciences, 2015)
This work was carried out to estimate the nutrient composition and methane production potential of various tree leaves to develop a database on methane production. Highest organic matter (OM) content was recorded in cashew leaves (96.87%) and lowest value was recorded in mulberry leaves (86.03%). Ether extract (EE) content of various tree leaves ranged from 0.54 to 8.74%. Neutral detergent fibre (NDF) was highest in velvel leaves (65.03%) and lowest in Murungai leaves (19.48%). Lowest in vitro true digestibility was observed in velvel leaves (41.59%) and highest value was observed in maramalli leaves (75.59%). Mulberry leaves had lowest methane production potential at half life (t1/2) (0.21 ml/100 mg truly digested substrate) and highest methane production potential at half life (t1/2) was recorded in velvel leaves (1.98 ml/100 mg truly digested substrate). Agathi leaves had highest (P